2005
DOI: 10.1002/fut.20148
|View full text |Cite
|
Sign up to set email alerts
|

The forecast quality of CBOE implied volatility indexes

Abstract: We examine the forecast quality of Chicago Board Options Exchange (CBOE) implied volatility indexes based on the Nasdaq 100 and Standard and Poor's 100 and 500 stock indexes. We find that the forecast quality of CBOE implied volatilities for the S&P 100 (VXO) and S&P 500 (VIX) has improved since 1995. Implied volatilities for the Nasdaq 100 (VXN) appear to provide even higher quality forecasts of future volatility. We further find that attenuation biases induced by the econometric problem of errors in variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(81 citation statements)
references
References 35 publications
6
73
0
2
Order By: Relevance
“…For their part, Corrado and Miller (2005) examined three US implied volatility indices namely VXN, VIX and VXO between January 1988 and December 2003. They found that the three implied volatility indices are efficient estimators of the stock market future volatility considering a GARCH modelling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For their part, Corrado and Miller (2005) examined three US implied volatility indices namely VXN, VIX and VXO between January 1988 and December 2003. They found that the three implied volatility indices are efficient estimators of the stock market future volatility considering a GARCH modelling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the earlier studies (Chiras and Manaster 1978;Christensen and Prabhala 1998;Christensen and Hansen 2002;Corrado and Miller 2005;Muzzioli 2007;Li and Yang 2009;Padhi and Shaikh 2013) conclude that implied volatility subsume all the information that contained in the historical volatility. The second strand of the literature on implied volatility index also supports the previous studies.…”
Section: Introductionmentioning
confidence: 97%
“…The VIX has proven to be very useful in forecasting the future market direction, especially during high volatile periods. Forecasting qualities of the VIX outperform traditional volatility measures based on historical realized volatility and GARCH models (Corrado andMiller, 2005 andCarr andWu, 2006). However, while the VIX could be used for hedging purposes, it could not easily be traded.…”
Section: Introductionmentioning
confidence: 99%